Positive and Negative Signals in Mast Cell Activation. Issue 9 (September 2017) - Bulfone-Paus, Silvia; Nilsson, Gunnar; Draber, Petr; Blank, Ulrich; Levi-Schaffer, Francesca
Abstract : Mast cells are powerful immune modulators of the tissue microenvironment. Within seconds of activation, these cells release a variety of preformed biologically active products, followed by a wave of mediator synthesis and secretion. Increasing evidence suggests that an intricate network of inhibitory and activating receptors, specific signaling pathways, and adaptor proteins governs mast cell responsiveness to stimuli. Here, we discuss the biological and clinical relevance of negative and positive signaling modalities that control mast cell activation, with an emphasis on novel FcεRI regulators, immunoglobulin E (IgE)-independent pathways [e.g., Mas-related G protein-coupled receptor X2 (MRGPRX2)], tetraspanins, and the CD300 family of inhibitory and activating receptors. Trends: Although IgE effector responses mediated by FcεRI on mast cells have been well studied, recent evidence supports the concept that the outcome of receptor triggering is complex and fine-tuned by several parameters and contributing coreceptors, leading to an intricate network of positive and inhibitory signals. In addition to dorsal root ganglia, the receptor MRGPRX2 is also expressed on mast cells, particularly in the skin, and reacts to basic peptides, such as neuropeptides, host defense peptides, and certain drugs, by inducing rapid degranulation. Tetraspanins have positive or negative regulatory roles in mast cell signaling pathways depending on the pathway and tetraspanin involved. The CD300 family of receptors has emerged as an important family containing both activating and inhibitory receptors. CD300a is the best-characterized member.